Baseline Levels of C-Reactive Protein and Proinflammatory Cytokines Are Not Associated With Early Response to Amisulpride in Patients With First Episode Psychosis: The OPTiMiSE Cohort Study. Issue 1 (27th May 2021) - Barbosa, Susana; Martinuzzi, Emanuela; Sommer, Iris E; Dazzan, Paola; McGuire, Philip; Arango, Celso; Diaz-Caneja, Covadonga M; Fleischhacker, Walter Wolfgang; Rujescu, Dan; Glenthøj, Birte; Winter-van Rossum, Inge; Kahn, René Sylvain; et al.
Abstract: Patients with a First-Episode of Psychosis (FEP) exhibit low-grade inflammation as demonstrated by elevated levels of C-reactive protein (CRP) and proinflammatory cytokines. The primary goal of this study was to investigate the association between proinflammatory biomarkers and clinical outcomes in unmedicated FEP patients. We used clinical data and biological samples from 289 FEP patients participating to the Optimization of Treatment and Management of Schizophrenia in Europe (OPTIMISE) clinical trial. Patients were assessed at baseline and 4–5 weeks after treatment with amisulpride. Baseline serum levels of interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, and CRP were measured. We first used multivariable regression to investigate the association between each of the 4 tested biomarkers and the following clinical outcomes: Positive and Negative Syndrome Scale (PANSS), Calgary Depression Score for Schizophrenia (CDSS), remission according to Andreasen's criteria, and Serious Adverse Events (SAEs). As a complementary approach, we used an unsupervised clustering method to stratify patients into an "inflamed" or a "non-inflamed" biotype based on baseline levels of IL-6, IL-8, and TNF-α. We then used linear and logistic regressions to investigate the association between the patient biotype and clinical outcomes. After adjusting for covariates and confounders, we did not find any association between IL-6, IL-8, TNF-α, CRP, or the patient biotype and clinical outcomes. Our results do not support the existence of an association between baseline levels of CRP and proinflammatory cytokines and early response to amisulpride in unmedicated FEP patients. ClinicalTrials.gov Identifier: NCT01248195.